2019
DOI: 10.3892/mco.2019.1868
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax following combination chemotherapy with bevacizumab: A case report and review of the literature

Abstract: Bevacizumab (BV) is a humanized monoclonal antibody that inhibits angiogenesis by targeting vascular endothelial growth factor (VEGF). The addition of BV to combination chemotherapy has been shown to improve the outcomes in several malignancies, including colorectal carcinoma (CRC). However, the use of BV has been associated with adverse effects, including hypertension, hemorrhage, proteinuria, delayed wound healing and bowel perforation. Pneumothorax (PTX) as an adverse event associated with BV use has rarely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In this case, the treatment for pneumothorax took approximately 1 month. However, there are also reports of other malignancies, including breast cancer, that require treatment for 2 months or more [ 8 ]. In advanced cases, bevacizumab in combination with chemotherapy is often introduced in the treatment of breast cancer, as it has been shown to have a high rate of tumor shrinkage and prolongation of progression-free survival [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the treatment for pneumothorax took approximately 1 month. However, there are also reports of other malignancies, including breast cancer, that require treatment for 2 months or more [ 8 ]. In advanced cases, bevacizumab in combination with chemotherapy is often introduced in the treatment of breast cancer, as it has been shown to have a high rate of tumor shrinkage and prolongation of progression-free survival [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The usual time frame, as reported in other case reports, is consistent with this case, wherein it occurred after four cycles of chemotherapy. Many chemotherapeutic agents (actinomycin-D, bevacizumab, bleomycin, carboplatin, cisplatin, cyclophosphamide, docetaxel, doxorubicin, erlotinib, etoposide, gefitinib, gemcitabine, paclitaxel, pemetrexed, oxaliplatin, vinblastine, vinorelbine) [ 19 , 20 ] have been implicated in causing pneumothorax. In our case, both doxorubicin and cyclophosphamide were used, and both drugs were incriminated as potential causative agents for pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 4 , the shared targets of apatinib and pazopanib include vascular endothelial growth factor receptors (VEGFRs) and stem cell factor receptor (KIT). We performed a literature search and found that bevacizumab and ramucirumab, single-target inhibitors of the VEGFR signaling pathway, can cause pneumothorax [ 21 23 ]. However, imatinib, which targets KIT but not VEGFRs (Table 4 ) [ 24 ], has not been reported to cause pneumothorax.…”
Section: Discussionmentioning
confidence: 99%